2002
DOI: 10.1038/nn797
|View full text |Cite
|
Sign up to set email alerts
|

A critical role for sonic hedgehog signaling in the early expansion of the developing brain

Abstract: The mechanisms that coordinate the three-dimensional shape of the vertebrate brain during development are largely unknown. We have found that sonic hedgehog (Shh) is crucial in driving the rapid, extensive expansion of the early vesicles of the developing midbrain and forebrain. Transient displacement of the notochord from the midbrain floor plate resulted in abnormal folding and overall collapse of the vesicles, accompanied by reduced cell proliferation and increased cell death in the midbrain. Simultaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 45 publications
7
86
0
2
Order By: Relevance
“…Our present results taken together with previous studies Britto et al, 2002;Ishibashi and McMahon, 2002;Corrales et al, 2006) suggest several mechanisms by which Gli transcription factors regulate tissue growth. At high levels of signaling, Shh can simply increase proliferation by upregulating GliA (primarily Gli2) such as in cerebellar granule cell precursors , and/or by downregulating Gli3R such as in the ventral midbrain .…”
Section: Research Articlesupporting
confidence: 86%
“…Our present results taken together with previous studies Britto et al, 2002;Ishibashi and McMahon, 2002;Corrales et al, 2006) suggest several mechanisms by which Gli transcription factors regulate tissue growth. At high levels of signaling, Shh can simply increase proliferation by upregulating GliA (primarily Gli2) such as in cerebellar granule cell precursors , and/or by downregulating Gli3R such as in the ventral midbrain .…”
Section: Research Articlesupporting
confidence: 86%
“…In addition, Spence et al (personal communication) have shown that Shh expressing retrovirus stimulates retinal regeneration from the CMZ of embryonic chicks. Despite the large number of studies demonstrating a role for Shh in regulation of proliferation during embryogenesis in both mammals and birds (see for review, Britto et al, 2002), one previous report failed to observe a mitogenic effect of Shh using replication-competent retroviral vector-mediated Shh up-regulation in embryonic chick explant cultures (Zhang and Yang, 2001a). There is one possible explanation for the differences between their assay and ours: mitogenic effects of growth factors are diminished when assayed in explant cultures as opposed to dissociated cultures (Lillien and Cepko, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Shh loss of function through notochord resection or cyclopamine treatment results in a failure of this expansion in chick and quail embryos. 16 Notochord removal, eliminating Hh signaling, was also found to increase the time for cell cycle traversal. It was suggested that this reflected lengthening of M and G 1 phases.…”
Section: Hh Signaling In the Growth And Evolution Of The Nervous Systemmentioning
confidence: 96%